DEVELOPMENT OF VERBAL-LOGICAL THINKING AMONG STUDENTS IN THE EDUCATIONAL PROCESS (Journal of Educational Sciences, 2018)
This article discusses the developed methodology for determining the criteria and levels of developmentof verbal-logical thinking among students in the learning process. The experimental work wascarried out in three stages: at the first stage, students were questioned and tested to identify the stateof the problem of the development of verbal-logical thinking; at the second experimental stage, a verifyingexperiment was conducted: input tests to identify the motivational, cognitive and praxeologicalcharacteristics of verbal-logical thinking. At the third stage, a structural-content model for developingstudents’ verbal-logical thinking in the learning process was developed and tested through the implementationof business games, situational assignments, and training. Development of verbal-logical thinkingof students is facilitated by the implementation of the following pedagogical conditions: the inclusionof students in activities to solve professional problems and the organization of joint development andimplementation of scientific works, the creative application of knowledge, manifested in the ability tosolve non-standard educational problems.Key words: verbal-logical thinking, teacher, student, vocational training, competence-based approach.